Science of Falling and Injury in Older Adults - Do All Falls Lead to Death?: Literature Review - Woochol Joseph Choi; Kitaek Lim; Seung-su Kim; Se-young Lee (Korean Research Society of Physical Therapy, 2021)
Understanding sciences behind fall-related hip fractures in older adults is important to develop effective interventions for prevention. The aim of this review is to provide biomechanical understanding and prevention strategies of falls and related hip fractures in older adults, in order to guide future research directions from biomechanical perspectives. While most hip fractures are due to a fall, a few of falls are injurious causing hip fractures, and most falls are non-injurious. Fall mechanics are important in determining injurious versus non-injurious falls. Many different biomechanical factors contribute to the risk of hip fracture, and effects of each individual factors are known well. However, combining effects, and correlation and causation among the factors are poorly understood. While fall prevention interventions include exercise, vision correction, vitamin D intake and environment modification, injury prevention strategies include use of hip protectors, compliant flooring and safe landing strategies, vitamin D intake and exercise. While fall risk assessments have well been established, limited efforts have been made for injury risk assessments. Better understanding is necessary on the correlation and causation among factors affecting the risk of falls and related hip fractures in older adults. Development of the hip fracture risk assessment technique is required to establish more efficient intervention models for fall-related hip fractures in older adults.